2011
DOI: 10.1021/jp201919r
|View full text |Cite
|
Sign up to set email alerts
|

Growth Dynamics of Nanocrystalline Diamond Thin Films Deposited by Hot Filament Chemical Vapor Deposition: Influence of Low Sticking and Renucleation Processes

Abstract: Nanocrystalline diamond (NCD) thin films are being progressively more employed in different applications. However, the current understanding of their growth mechanisms, which becomes important to properly tune their properties, is still very limited. In this context, we have studied by atomic force microscopy the growth dynamics of NCD thin films grown on micro-and nanoseeded silicon substrates by hot filament chemical vapor deposition for different methane/hydrogen gas mixtures. The NCD film growth dynamics d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 63 publications
2
19
1
Order By: Relevance
“…This is fully in line with the outcomes of several previous studies 43,66,67 that showed that the absolute value of the RMS roughness of nanograined diamond films depends both on the gas mixture and the primary nucleation site density.…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 92%
See 3 more Smart Citations
“…This is fully in line with the outcomes of several previous studies 43,66,67 that showed that the absolute value of the RMS roughness of nanograined diamond films depends both on the gas mixture and the primary nucleation site density.…”
Section: Acs Paragon Plus Environmentsupporting
confidence: 92%
“…[43][44][45] In fact, all the synthesized NCD films in this study are of a lower crystalline order than the strongly faceted NCD films with high purity grown from extremely high diamond seed densities and carbon-lean gas atmosphere, 2 and they are commonly referred to as 'ballas' or cauliflower-type diamond. 2,39 The smoothest NCD films with most uniform surface morphology were grown on the Mo, Nb, and W metallic thin films (Figures 7b, 7c, and 7f, respectively).…”
Section: Growth Of Smooth and Dense Ncd Filmsmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, studies have investigated the use of UNCD as a MEMS material. 15) Although a few researchers have used a hot filament CVD apparatus for the synthesis of the UNCD, 16) most of the samples have been synthesized by a microwave plasma CVD apparatus. 17) Moreover, Si was used as the substrate in the CVD process.…”
Section: Introductionmentioning
confidence: 99%